Recent advances and future directions in ophthalmologic neuroimaging. (June 2009) - Gadani, Sameer; Truwit, Chip; McKinney, Alexander M
Advances in neuroimaging over the past 5–10 years have offered opportunities to address challenging and previously unanswered clinical questions in ophthalmologic neuroimaging. Among these advances are diffusion-weighted imaging, diffusion-tensor imaging (DTI), perfusion MRI (PWI), functional MRI (fMRI) as well as single-photon emission tomography, PET scanning and high-frequency contrast harmonic ultrasound imaging. The MRI techniques are based on imaging the static or dynamic changes of the hydrogen proton in a controlled magnetic field. Diffusion-weighted imaging, for instance, offers temporal characterization of acute infarction and differentiation of neoplasm from bacterial abscess, or differentiation between certain types of neoplasms that may present with visual symptoms. The addition of PWI allows rapid assessment of tissue at risk (penumbra) beyond the core (umbra) in the setting of acute stroke. PWI, computed tomography perfusion and high-frequency contrast harmonic imaging are used to study the perfusion characteristics of the ocular tumors for determination of their prognosis. PWI is also being studied for its utility in histopathologic grading of intracranial tumors. DTI and fMRI offer new insights into presurgical planning of the brain tumor resection. DTI helps to identify the retrochiasmatic optic pathways. Importantly, such fibertracking by DTI enables the differentiation of invasive from displacing lesions. fMRI is also being studied for its utility to identify retinotopic borders, motion processing, visual attention and patients with visual defects. Furthermore, the combination of both fiber tracking and fMRI offers the opportunity to demonstrate not only spatial networks within the brain but also temporal activation and recruitment of components of such networks. Single-photon emission tomography and PET scanning are helpful for the noninvasive estimation of the cerebral visual function, as well as the evaluation of functional recovery in patients. With these advancements, neuroradiology continues to lead the transition of diagnostic imaging from anatomic to physiologic and molecular imaging.